2017
DOI: 10.18632/oncotarget.16164
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite dominates sodium nitroprusside-induced apoptosis in human hepatocellular carcinoma cells

Abstract: This study aims to explore which radicals dominate sodium nitroprusside (SNP)-induced cytotoxicity in human hepatocellular carcinoma (HCC) cells (HepG2 and Hep3B). Exposure of SNP to cell medium produced abundant nitric oxide (NO), superoxide anion (O2·−), hydrogen peroxide (H2O2) and iron ions. SNP potently induced caspases activation, mitochondrial membrane permeabilization and apoptosis in HCC cells. In Hep3B cells, pretreatment with NO scavenger (PTIO) did not prevent SNP-induced cytotoxicity. However, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Based on our recent finding that ONOO ─ from the reaction between NO and O2· − dominated the sodium nitroprusside (SNP)-induced apoptosis in HepG2 cells [ 49 ], we speculated that ONOO ─ might dominate the synergistic chemo-photothermal anti-cancer effect of nGO-PEG-ARS. As expected, FCM analysis with DHR 123 staining showed that nGO-PEG-ARS treatment for 6 h potently induced abundant ONOO ─ generation which was significantly enhanced by NIR irradiation (Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our recent finding that ONOO ─ from the reaction between NO and O2· − dominated the sodium nitroprusside (SNP)-induced apoptosis in HepG2 cells [ 49 ], we speculated that ONOO ─ might dominate the synergistic chemo-photothermal anti-cancer effect of nGO-PEG-ARS. As expected, FCM analysis with DHR 123 staining showed that nGO-PEG-ARS treatment for 6 h potently induced abundant ONOO ─ generation which was significantly enhanced by NIR irradiation (Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…ROS and ONOO ─ generations inside living cells were measured by FCM with an oxidation-sensitive probe 2′, 7′-dichlorodihydrofluorescein diacetate (DCF-DA, Sigma, USA) and Dihydrorhodamine 123 (DHR 123, Wuhan, Aimeijie) as described previously [ 49 ]. DCF-DA is cleaved by nonspecific esterases and becomes highly fluorescent DCF upon oxidation by ROS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the previous report that SNP ( 500 lM) was toxic to mammalian cells. 33,37 However, it is interesting that there observed SNP induced cytotoxicity discrepancy between Acanthamoeba and HCECs. Exposure to 100 lM of SNP for 3 days induced only 30% of cytotoxicity on HCEC, whereas >90% of Acanthamoeba were killed under the same condition.…”
Section: Discussionmentioning
confidence: 99%
“…Введення L-аргініну, напроти, не впливало на цей показник і запобігало підвищенню СОД активності під впливом CdCl2. Різні ефекти донорів NO на активність СОД можна пов'язати з появою АФК за введення SNP, під час спонтанного розкладання якого разом з NO утворюються також іони заліза, пероксид водню і супероксид-аніон (Quan et al, 2017).…”
Section: таблицяunclassified